2008
DOI: 10.1007/s00408-008-9078-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Cells Participate in Stromal Remodeling of the Lung Following Acute Bacterial Pneumonia in Mice

Abstract: Bone marrow-derived cells (BMDC) have been shown to graft injured tissues, differentiate in specialized cells, and participate in repair. The importance of these processes in acute lung bacterial inflammation and development of fibrosis is unknown. The goal of this study was to investigate the temporal sequence and lineage commitment of BMDC in mouse lungs injured by bacterial pneumonia. We transplanted GFP-tagged BMDC into 5-Gy-irradiated C57BL/6 mice. After 3 months of recovery, mice were subjected to LD 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…As the response subsided, PBMC telomere length ratio in the MMA-SS group returned to control levels at 3 and 10 d before increasing at 30 d, suggesting either a biphasic response or changes in cell populations. In other types of lung injury, bone marrow-derived progenitor cells have been observed to move into the lungs and are involved in lung repair (Serikov et al, 2008; Yamada et al, 2004). The influx of bone marrow-derived, stem-like cells may have altered overall telomere length.…”
Section: Discussionmentioning
confidence: 99%
“…As the response subsided, PBMC telomere length ratio in the MMA-SS group returned to control levels at 3 and 10 d before increasing at 30 d, suggesting either a biphasic response or changes in cell populations. In other types of lung injury, bone marrow-derived progenitor cells have been observed to move into the lungs and are involved in lung repair (Serikov et al, 2008; Yamada et al, 2004). The influx of bone marrow-derived, stem-like cells may have altered overall telomere length.…”
Section: Discussionmentioning
confidence: 99%
“…In our initial observation, we defined the beneficial effects of the systemic administration of mesenchymal stem cells to control ARDS mainly by their anti-inflammatory properties. Multiple groups have reported similar observations where the protective effect has been demonstrated in different animal models and human ex-vivo lungs [17-22]. The protective effects of mesenchymal stem cells are attributed to several mechanisms including secretion of the anti-inflammatory cytokines IL-10 and TGF-β, and Keratinocyte Growth Factor (KGF) and elaboration of antibacterial peptides.…”
Section: Introductionmentioning
confidence: 87%
“…13,24 A growing number of studies have shown that MSCs have immunomodulatory and anti-infl ammatory eff ects despite minimum or absent engraftment. [25][26][27][28] Consequently, research has shifted towards identifi cation of alternative pathways through which MSCs interact with host tissue, including interactions between cells, direct interactions with the host immune system, and mitochondrial transfer. The pathway with the most robust supporting evidence is the ability of MSCs to coordinate tissue repair through the release of soluble paracrine factors.…”
Section: Reviewmentioning
confidence: 99%